PENGARUH MORALITAS INDIVIDU, KOMITMEN ORGANISASI DAN TRANSPARANSI PENGELOLAAN KEUANGAN TERHADAP KECURANGAN BUMDES DI KECAMATAN DAWAN KLUNGKUNG - Rai Dwi Andayani W; I Komang Adnyana (Universitas Boyolali, 2023)
This study aims to determine the effect of individual morality, organizational commitment and transparency of financial management on Village Enterprises Fraud (DUMDes) in Dawan Klungkung District. The population in this survey is all BUMDes employees in Dawan Klungkung Regency. There are still 10 BUMDes with a total of 101 employees. The sample size of this study was 101 people and was tested using multiple linear regression analysis techniques. The results of this study indicate that fraud can be overcome by increasing individual morality. Increasing organizational commitment will reduce the level of fraud. if transparency can be carried out then fraud in the organization can be avoided.